Incomplete Regulations of Mediator Competence Standards As A Requirement For Members of Consumer Dispute Resolution Agencies - Rayhan Rizky Fitrianto; Hamidi Masykur; Yenny Eta Widyanti (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
This thesis examines the incompleteness of the mediator competency standards set in the Minister of Trade Regulation No. 72 of 2020 as a requirement for members of the Consumer Dispute Resolution Agency (BPSK). The regulation does not explicitly stipulate mandatory training or certification of mediators for BPSK members, thus opening up the possibility of mediation being carried out by parties without a legal background or mediation skills. This has an impact on the low quality of dispute resolution, injustice for the parties, and decreased public trust in BPSK as a dispute resolution institution. This study uses a normative juridical method with a statutory, conceptual, and comparative approach. Based on the analysis, the absence of mediator competency regulations causes legal uncertainty (Gustav Radbruch's Theory of Legal Certainty) and violations of the principle of distributive justice (Aristotle). As a solution, this thesis recommends the reconstruction of Minister of Trade Regulation No. 72 of 2020 by adopting the German legal system model, namely requiring mediator certification and the imposition of administrative sanctions for violations. This proposal is in line with the civil law system and Philipus M. Hadjon's theory of authority, which emphasizes the importance of proportionality and professionalism in the implementation of public authority.